Novel three-dimensional acellular dermal matrix for prepectoral breast reconstruction: First year in review with BRAXON®Fast - Berna, Giorgio; De Grazia, Alessia; Antoniazzi, Elisa; Romeo, Marco; Dell’Antonia, Francesco; Lovero, Stefano; Marchica, Paolo; Rizzetto, Christian; Burelli, Paolo (Frontiers in Surgery, 2022)
Implant-based breast reconstruction is gaining worldwide popularity as a standard tool in breast cancer treatment. As personalized medicine evolves, surgeons’ commitment aims at increasingly optimized reconstructive procedures to ensure highly biocompatible materials and enhanced aesthetic-functional results. Acellular dermal matrices (ADMs) are collagen-based materials that have greatly helped this purpose in the last twenty years, firstly improving submuscular techniques and ultimately making prepectoral implant placement possible thanks to their bioactive anti-fibrosis action. Currently available technologies have recently produced the first three-dimensional biological matrices for a time-saving complete wrapping of the synthetic prosthesis, thus creating a total biological interface on the implant with patient's tissues. Here we report our experience on the first 23 eligible patients who received 3DADM-assisted prepectoral reconstruction. On a total of 27 breasts, overall complication rate was 11.1%, including one minor seroma (3.7%), one case of necrosis (3.7%) and one implant removal due to infection. As new-generation devices, 3D ADMs showed an effective performance allowing to reduce overall exposure time for implant preparation and proved an optimal safety profile.